2020
DOI: 10.2807/1560-7917.es.2020.25.16.1900457
|View full text |Cite
|
Sign up to set email alerts
|

Two multi-fragment recombination events resulted in the β-lactam-resistant serotype 11A-ST6521 related to Spain9V-ST156 pneumococcal clone spreading in south-western Europe, 2008 to 2016

Abstract: Two multi-fragment recombination events resulted in the β-lactam-resistant serotype 11A-ST6521 related to Spain9V-ST156 pneumococcal clone spreading

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…A previous study from our group ( 28 ) reported persistence of serotype 14 related to CC156; however, in the present study, a significant decrease of serotype 14, mainly in the <5-year-old children and ≥65-year-old adults, was observed. Interestingly, while serotype 14 decreased, serotype 11A related to ST6521, a double locus variant included in CC156, experienced a modest increase that could be associated with capsular switching ( 33 ). Monitoring of the evolution of these serotypes related to CC156 seems relevant for future vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study from our group ( 28 ) reported persistence of serotype 14 related to CC156; however, in the present study, a significant decrease of serotype 14, mainly in the <5-year-old children and ≥65-year-old adults, was observed. Interestingly, while serotype 14 decreased, serotype 11A related to ST6521, a double locus variant included in CC156, experienced a modest increase that could be associated with capsular switching ( 33 ). Monitoring of the evolution of these serotypes related to CC156 seems relevant for future vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a significantly high frequency of serotype 11A isolates causing non-BPP episodes. Studies on IPD show a low frequency of episodes caused by this serotype [33] but this is not the case when we look at other pneumococcal diseases. For instance, serotype 11A is a frequent serotype causing acute exacerbations and pneumonia in patients with chronic obstructive pulmonary disease (COPD) [34,35].…”
Section: Discussionmentioning
confidence: 80%
“…In fact, serotype 11A is also frequent in carriage suggesting a low invasive disease potential [36,37]. An increase in serotype 11A isolates has been reported in Europe after the introduction of PCVs [33] due to the emergence of a new lineage related to the Spain 9V -156 clone (PMEN3). As this clone shows characteristically β-lactam resistance with high amoxicillin MICs (4-8 mg/L) [38], its significant frequency among non-BPP episodes should be taken into account when choosing empirical oral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the emergence of penicillin-resistant strains of serotype 11A is concerning from a pathogenesis perspective [34]. The invasive disease potential of this serotype is highly related to the rise of genotype ST6521 11A that has spread across Europe in the last years, becoming one of the most prevalent within serotype 11A [35]. This genotype of serotype 11A is associated with high levels of antibiotic resistance, shows a greater ability to form biofilms and avoids very efficiently the host immune response [34].…”
Section: Discussionmentioning
confidence: 99%